Analytical Study of the Novel "Tawoos Faqat Rang" in the Perspective of 9/11 - Khan, Izhar; Ali, Anwar (sourcecoder, 2022)
Neelam Ahmed Bashir is the eldest daughter of Ahmed Bashir. She is a fiction writer and poet, she writes in Urdu and Punjabi. Neelum mostly resides in USA where all her three kids are living. Neelam Ahmed Bashir is a well-known novelist. Neelam Ahmed Bashir herself started writing very late, but she says that her home environment was a major factor in her entry into the world of science and literature. Neelam Ahmed Bashir’s first book was Rose Street. Subsequent books include ’Jagan’s Caravan’, ’Le Sans Bhi Aastha’, ’Satmagar September’ ’Ek Thi Malaka’. & ’Char Chand’, in which he has presented personal sketches. Neelam Ahmad Bashir was a Prominent Pakistani story writer and novelist. She is well known for her contributions in today’s Urdu literary scene. She writes candidly and fearlessly on controversial and bold subjects. Neelam Ahmad Bashir is a prestigious name in the world of Urdu fiction. "Taos faqat rang" in her first novel, which is the lament of American society. In this novel the tragedy of 9/11 has also been made a topic among other topics. The tragedy of 9/11 affected literature along with other fields. And Neelam Ahmad Bashir tried to explain the various theories related to this incident which are known in the world.